Cell phone advertising delivery acceptance: development, purification and validation of the advertising delivery acceptance scale. (6th August 2008) - Saran, Anshu; Cruthirds, Kevin W.; Kalliny, Morris; Minor, Michael
This paper describes the development, purification and validation of a short reliable self-report scale designed to measure the concept of delivery acceptance of advertising over cell phones. There is limited literature on this subject of advertising acceptance and a measurement scale has eluded the academicians and practitioners, which could help measure the acceptance of the receipt and use of ads over mobile telephony, thereby helping marketers decide on the level and type of ads by market segmentation. Five data sets were employed using 793 surveys, two focus groups and six individual interviews which helped develop, purify and validate the six-item Likert-type one-dimensional scale. The research has attempted to provide evidence for dimensionality, reliability and validity. The scale could be used by academicians and practitioners alike, replacing single items to measure the concept.